Measurement of the ventriculoatrial interval from the coronary sinus during para‐Hisian pacing may fail to distinguish ventriculoatrial nodal conduction from conduction over a septal accessory pathway. Issue 1 (4th July 2014) - Iijima, Takafumi; Kaneko, Yoshiaki; Nakajima, Tadashi; Irie, Tadanobu; Ota, Masaki; Saito, Akihiro; Kurabayashi, Masahiko
Abstract: Background: Para‐Hisian pacing (PHP) helps differentiate retrograde conduction over an accessory pathway (AP) from retrograde conduction over the atrioventricular (AV) node. This study examined a potential limitation of this technique, focusing on the measurement of the ventriculoatrial (V–A) interval from the coronary sinus (CS) during PHP. Methods: Our subjects were 9 patients undergoing electrophysiological studies before successful catheter ablation of a posteroseptal AP. During PHP, retrograde conduction occurred over an AP when the pacing stimulus to atrium (S–A) interval recorded near the AP remained unchanged whether the His bundle (HB) was captured or not (pattern 1), or when a loss of HB capture was associated with an increase in the S–A interval and no change in the V–A interval near the AP (pattern 2). Results: Patterns 1 and 2 were observed in 5 (56%) and 2 (22%) patients, respectively. However, in the remaining 2 patients (22%), loss of HB capture during PHP was associated with an increase in the S–A interval (as in pattern 2), whereas the V–A interval near the AP could not be measured because no ventricular electrogram was visible on the CS recording (pattern 3); therefore, the presence of AP could not be confirmed by PHP. In patterns 2 and 3, the atrial activation sequence remained unchanged whether the HB was captured or not. Conclusions: PHP may not be able to discriminate between a retrograde septal AP and AV nodal conduction in patients whose proximal CS recording shows no visible ventricular electrogram.